Application of fuzzy comprehensive evaluation method in the identification of potential faults of high-voltage power cables - Fu, Han; Ai, Yuhao; Qiu, Long; Ai, Yonghen; Yang, Bin; Shi, Yihui (Frontiers in Energy Research, 2024)
To address the challenge of identifying hidden faults in high-voltage power cables, this study proposes a fuzzy comprehensive evaluation method. The method aims to provide a comprehensive and effective means of fault identification for operation and maintenance personnel. The fuzzy comprehensive evaluation method involves several key steps. Firstly, relevant indices are selected from operation monitoring data of high-voltage cables to form a comprehensive evaluation factor set. This set is then matched with an evaluation set established according to corresponding operation guidelines. Secondly, membership functions are established using the triangular distribution function to calculate the cable fault evaluation set. Thirdly, the weights of the evaluation factors are quantified using the analytical hierarchy process. To demonstrate the effectiveness of the proposed method, a fault analysis of a city’s 220 kV double-circuit cable system is conducted. The results show that the fuzzy comprehensive evaluation method can accurately identify faults in the cable system. The proposed fuzzy comprehensive evaluation method provides a valuable reference for operation and maintenance personnel in identifying hidden faults in high-voltage power cables.